Identifying Psychopathy Subtypes Using a Broader Model of Personality: An Investigation of the Five Factor Model Using Model-Based Cluster Analysis - Falkenbach, Diana M. (Journal of interpersonal violence, 2021)
The field of psychopathy research largely argues that the disorder is a heterogeneous concept with two predominant subtypes: primary psychopathy and secondary psychopathy. Early research examined psychopathy subtypes in terms of traits specific to psychopathy. However, recent research suggests that psychopathy may be conceptualized more dimensionally as an extreme variation in normative personality traits. This concept propels the examination of psychopathy using a broader model of personality, the Five Factor Model. Using model-based cluster analysis, this study uses the Five Factor Model to identify subtypes. Utilizing an American college sample, a cluster analysis was performed on the highest third of Psychopathic Personality Inventory (PPI)-Total scorers using the Neuroticism Extraversion Openness Personality Inventory–Revised (NEO-PI-R) domains. This analysis yielded a two-cluster solution, with one cluster representing Primary psychopathy and the other representing Secondary psychopathy. The two clusters displayed differences in Neuroticism, Conscientiousness, Openness, and Extraversion, which may be important for understanding psychopathy subtyping using general personality traits. Associated traits such as aggression, anxiety, and borderline traits largely match other subtyping research. Overall, the results support the existence of psychopathy variants in a nonoffending sample, the dimensionality of psychopathy, and the ability of normative personality traits to differentiate psychopathy subtypes. Unveiling the complex nature of psychopathy through illumination of its dimensions has strong implications for future research as it can help specify an otherwise elusive disorder. Such desired specification can reveal psychopathy’s etiology and potential treatment options. The results of this research in particular suggest a link between profiles of normal personality traits and aggressive behavior indicating the potential for risk assessment. Moreover, this research provides evidence for psychopathy’s dimensionality versus categorical casting, contributing to the debate about mental disorder classifications in general.